Evaluating Thyroid Function in Obese Adults in Dhi Qar, Iraq - Dakhil, Kareema A. (Indonesian Journal on Health Science and Medicine, 2025)
Obesity is a global public health challenge with profound endocrine and metabolic implications, particularly affecting the thyroid axis, which regulates basal metabolic rate and energy expenditure. Emerging evidence suggests that obese individuals may exhibit altered thyroid function even in the absence of overt thyroid disease. Despite existing studies, limited data are available from Iraq regarding the impact of obesity and aging on thyroid hormone profiles. This study aimed to evaluate thyroid hormone levels—TSH, free T4, and free T3—in obese adults across two age groups and compare them with non-obese healthy controls in Dhi Qar, Iraq. A cross-sectional study of 180 male participants revealed significant hormonal alterations. Elderly obese individuals (Group B, 60–75 years) had the highest TSH levels (4.16 ± 1.25 μIU/mL), followed by younger obese adults (Group A, 35–45 years, 3.45 ± 1.10 μIU/mL), compared with healthy controls (2.12 ± 0.80 μIU/mL). Both obese groups exhibited reduced fT4 and fT3 levels, most pronounced in elderly subjects (0.86 ± 0.14 ng/dL and 2.25 ± 0.30 pg/mL, respectively). This is one of the first studies in Iraq to demonstrate a recurrent association between obesity, age, and thyroid hormone dysregulation, pointing to subclinical hypothyroidism. The findings underscore the importance of routine thyroid function screening in obese individuals, particularly the elderly, for early detection and prevention of endocrine complications. Highlights: Pseudomonas aeruginosa effectively removed up to 70% of organic pollutants (COD) and over 60% of nitrogen compounds from wastewater. The bacteria showed high heavy metal removal efficiency, with 87.2% for nickel and 77.5% for zinc. Nitrate removal was the lowest (30.3%), highlighting the need for optimized treatment conditions to improve efficiency.